Safe sesame (Sesamum indicum L.) production : Perspectives, practices and challenges: SAFE SESAME PRODUCTION : PERSPECTIVES, PRACTICES AND CHALLENGES - H H KUMARASWAMY; J JAWAHARLAL; A R G RANGANATHA; S CHANDER RAO (Journal of Oilseeds Research, 2015)
Sesame seed is a reservoir of nutritional components with numerous beneficial effects for health promotion in humans. In order to complement efforts to boost sesame production and thereby enhancing economic returns to sesame growersthrough itssupply to meet the growing demand in domestic as well asin international market, there is an urgent need to address an important issue i.e.,safe sesame production. Here, we have adopted two approachesaspects and dimensions - to analyze perspectives of safe sesame, with the objective of achieving comprehensive understanding of various issues and considerations related to safe sesame production and its human consumption. Apartfromtwo dimensions- human health and trade -, there are mainly two aspects ofsesame being considered safe. The first aspect is concerned with how safe is sesame seed or oil for human consumption in terms of its nutritional components including the absence of anti-nutritional factors. The second is regarding the absence of chemicals, infectious pathogens and other contaminants that may pose threat to human health. In this paper, we have analyzed the available literature, related to safe sesame production, in the light of eight considerations: (1) Human nutrition, (2) Meteorology, (3) Genotype, (4) Technology, (5) Crop management, (6) Plant health management, (7) Harvest and post-harvest handling and (8) Challenges.